An Institutional Perspective on the Number of Stent Retriever Pass and Rate of Recanalization in Mechanical Thrombectomy for Acute Ischemic Stroke: When to Stop? - Bheru Dan Charan,; Gaikwad, Shailesh B; Jain, Savyasachi; Garg, Ajay; Devarajan Sebastian, Leve Joseph; Srivastava, MV Padma; Bhatia, Rohit; Pandit, Awadh Kishore; Kale, Shashank Sarad (Acta medica Lituanica, 2024)
Background and purpose: Mechanical thrombectomy is the standard treatment modality for flow restoration in acute ischemic stroke. In cases of persistent occlusion, the optimal number of retrieval attempts before considering procedure termination is currently undetermined and is a topic for research. Therefore in this study, we studied the impact of the number of stent retrieval maneuvers on the recanalization of vessels.Methods: In this retrospective single-center observational study we included 52 patients with large vessel occlusion who underwent stent retriever mechanical thrombectomy. Successful recanalization rate was defined as modified TICI (Thrombolysis in Cerebral Infarction) 2b or 3.Result: The overall successful recanalization rate was 44.24%. The recanalization rate per stent retrieval attempt was the highest in 1st attempt (28.84%) and no recanalization was observed with the 3rd, 5th, and 6th attempts (p
Keywords: Recanalization; ischemic stroke; Mechanical thrombectomy